2016
DOI: 10.21548/31-2-1418
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation-derived Aroma Compounds in Varietal Young Wines from South Africa

Abstract: The volatile composition of 925 single cultivar young Sauvignon blanc, Chardonnay, Pinotage, Merlot, Shiraz and Cabernet Sauvignon wines of vintages 2005 to 2007, was determined using gas chromatography -flame ionisation detection. Compositional data were compared to published data on young wines from South Africa and other countries. South African young wines analysed in this study had a largely similar volatile composition to that reported in the literature. Significant between-vintage and between-cultivar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
7
27
1
Order By: Relevance
“…The concentration of the seven volatile fatty acids identified in the samples were consistent with those previously reported [13,17], and most of them exceeded their respective olfative threshold values. Fatty acids are related to creamy, cheese and rancid notes, and at low concentrations give pleasant notes and contribute to the overall complexity of wines.…”
Section: Resultssupporting
confidence: 89%
“…The concentration of the seven volatile fatty acids identified in the samples were consistent with those previously reported [13,17], and most of them exceeded their respective olfative threshold values. Fatty acids are related to creamy, cheese and rancid notes, and at low concentrations give pleasant notes and contribute to the overall complexity of wines.…”
Section: Resultssupporting
confidence: 89%
“…Concentrations and the composition of wine major aroma compounds produced during fermentation, such as alcohols, straight-chain acids, and ethyl and acetate esters, were in a fair agreement with those found in the three varieties investigated earlier (22,23,30,31,51), and it was confi rmed that they make up a basis of the aroma profi le of unoaked young white wines. They depend mostly on fermentation parameters and conditions, although physicochemical composition of must may have a certain infl uence (52).…”
Section: Fermentation Aroma Compoundssupporting
confidence: 73%
“…Several studies reported that fermentation aroma compound composition signifi cantly depends on varietal origin and harvest year, and can be useful in diff erentiating wines on the basis of these two criteria (7,37). This especially refers to medium-chain fatty acids and their ethyl esters which, unlike acetates, depend more on the availability of substrates, and therefore agricultural conditions and variety, than on enzymatic activity of yeast (31). For example, it was shown that South African unoaked young Chardonnay wines can be discriminated from other varieties (correct classifi cation of 74 %) on the basis of 2-phenylethanol, diethyl succinate, ethyl hexanoate, ethyl decanoate, ethyl octanoate, hexyl acetate and 1-propanol concentrations (31).…”
Section: Fermentation Aroma Compoundsmentioning
confidence: 99%
“…The highest concentration of free fatty acids was observed in Vidal wine, where concentrations of hexanoic and octanoic acids reached 12.2 and 38.1 mg/L, respectively (Table 3). These values are relatively high compared to reported values for V. vinifera white wine with reported concentration ranging from 0.05 mg/L in Chardonnay to 13.7 mg/L in Sauvignon Blanc, for hexanoic acid, and from non-detectable to 12.2 mg/L in Sauvignon Blanc, for octanoic acid [42,43].…”
Section: Fatty Acid Ethyl Esters and Free Fatty Acidscontrasting
confidence: 58%